2019
DOI: 10.7866/hpe-rpe.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Macroeconomic Stability in South Asian Countries

Abstract: The objective of this study is to analyze the relationship between fiscal policy and macroeconomic stability in South Asian countries. Specific objectives of the study are to analyze the effects of major macroeconomic variables on macroeconomic stability and to analyze the channels i.e. automatic stabilizer, cyclical fiscal policy, and discretionary fiscal policy through which fiscal policy contributes to macroeconomic stability. The study has used Keynesian model which states that in order to stimulate aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…It is not new that the financial sector has an important role in a country's economy (Munir & Riaz, 2019). In many developing countries, where the banking sector still dominates the financial sector (bank-based), banks hold the main intermediary positions necessary for economic growth.…”
Section: Literature Review Banking Stabilitymentioning
confidence: 99%
“…It is not new that the financial sector has an important role in a country's economy (Munir & Riaz, 2019). In many developing countries, where the banking sector still dominates the financial sector (bank-based), banks hold the main intermediary positions necessary for economic growth.…”
Section: Literature Review Banking Stabilitymentioning
confidence: 99%
“…Scholars examine the dynamic relationship between foreign investment inflows and a country's overall economic development (Toyin, & Oludayol, 2020). Noteworthy is the work that examines in detail the relationship between macroeconomic stability and fiscal policy, which can be both cyclical and discretionary (Munir, K., & Riaz, N., 2019). Also, scientists (Stanciu, 2019) have built a causal chain based on financial stability as a result of macroeconomic stability and economic security of the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fiscal policy has the potential to be beneficial in boosting aggregate demand and reviving a sluggish economy, according to one of the fundamental principles of macroeconomics (Munir & Riaz, 2019;. The possible impact of fiscal policy on the growth of the financial sector is a neglected issue, nevertheless.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also looked into the relationship between several other variables and fiscal policy. This study involves Munir and Riaz (2019), who found that monetary and fiscal policies in the sub-region had a favorable impact on economic growth. Rodriguez (2014) evidenced that lower mean growth will come from higher volatility in a credit-constrained economy, especially if the fiscal policy is pro-cyclical and the country is less developed financially.…”
Section: Introductionmentioning
confidence: 99%